2002
DOI: 10.1111/j.1574-6968.2002.tb11106.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the glutamic and aspartic residues in Na+-ATPase function in theZrENA1gene ofZygosaccharomyces rouxii

Abstract: The effect of replacement of negatively charged amino acid residues on the function of Na+ transport proteins of the salt-tolerant yeast Zygosaccharomyces rouxii was examined by heterologous expression of mutant proteins in a strain of Saccharomyces cerevisiae, RH16.6, that lacks native Na+-ATPase activity due to null mutations of ENA1, ENA2, ENA3, and ENA4. Mutants of Na+/H+ antiporter gene (ZrSOD2) and Na+-ATPase gene (ZrENA1) of Z. rouxii were generated by site-directed mutagenesis. The significance of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These residues are conserved in the antiporters of prokaryotes and of some lower eukaryotes, despite an overall low similarity in their primary sequences (28). The tandem of aspartyl residues identified in the Spsod2p study were shown to be vital for the function of the Z. rouxii Sod2 antiporter (Asp 265 -Asp 266 ) (31), and mutations of conserved aspartyl residues 266 and 267 to asparagine reduced the sodium transport activity also in C. albicans Cnh1p and S. cerevisiae Nha1p (17,26). Interestingly, in the case of ScNha1 (D266,267N) antiporter, the potassium efflux activity was not changed, and it was another aspartyl residue (Asp 241 ) whose mutation affected K ϩ extrusion (26).…”
Section: Namentioning
confidence: 99%
“…These residues are conserved in the antiporters of prokaryotes and of some lower eukaryotes, despite an overall low similarity in their primary sequences (28). The tandem of aspartyl residues identified in the Spsod2p study were shown to be vital for the function of the Z. rouxii Sod2 antiporter (Asp 265 -Asp 266 ) (31), and mutations of conserved aspartyl residues 266 and 267 to asparagine reduced the sodium transport activity also in C. albicans Cnh1p and S. cerevisiae Nha1p (17,26). Interestingly, in the case of ScNha1 (D266,267N) antiporter, the potassium efflux activity was not changed, and it was another aspartyl residue (Asp 241 ) whose mutation affected K ϩ extrusion (26).…”
Section: Namentioning
confidence: 99%